THE DEVELOPMENT OF DIAGNOSTICS TEST FOR ELICITING STUDENTS’ MENTAL MODEL ABOUT SOLUBILITY EQUILIBRIA - Wiji, Wiji; Rahmi, Chusnur; Mulyani, Sri; Widhiyanti, Tuszie (Jurnal Pengajaran MIPA, 2018)
Eliciting students’ mental model will enable teachers to monitor their students’ learning and understanding students’ mental model is a growing area of scientific inquiry in chemistry education. Diagnostics test can help teachers to understand the state of students’ understanding about certain topics and therefore, we developed a diagnostics test for eliciting students’ mental model about solubility equilibria. The developed diagnostics test was specifically designed to elicit mental model and rooted in Predict-Observe-Explain scheme, hence we called it as DTM-POE. After a series of DTM-POE trials, implementation results suggested that the developed DTM-POE can elicit students’ mental model about solubility equilibria. Several types of students’ mental models were found and DTM-POE sensitivity to elicit these mental models is discussed.